(untitled) (Al Basirah, 2023)
This research paper explores the principles, methods, and responsibilities related to environmental purification, as elucidated in the Sirah (biography) of the Prophet Muhammadﷺ. Drawing upon historical accounts and primary sources, the study delves into the Prophet’s exemplary practices and teachings concerning environmental conservation, sustainable living, and ecological responsibility. The research highlights key rules derived from the Sirah that emphasize the sanctity of nature, the preservation of biodiversity, and the promotion of sustainable resource management. It examines the Prophet’s teachings on concepts such as moderation, stewardship, and accountability, which encourage believers to adopt a balanced and harmonious approach towards the environment. Additionally, the paper investigates the practical methods employed by the Prophet in maintaining cleanliness, managing waste, and utilizing resources responsibly, providing valuable insights for contemporary environmental practices. Furthermore, the research emphasizes the collective responsibility of individuals, communities, and societies in preserving and protecting the environment, as exemplified by the Prophet’s efforts to instill environmental consciousness among his followers. By analyzing the environmental aspects of the Sirah, this research sheds light on the Islamic perspective on environmental purification, offering practical guidelines and lessons for addressing contemporary environmental challenges. Ultimately, the findings of this study contribute to the understanding of Islamic environmental ethics and inspire individuals and communities to adopt responsible practices that promote environmental sustainability and stewardship, aligning with the timeless teachings of the Prophet Muhammadﷺ.